PERANAN SEWA FLOOR DISPLAY TERHADAP PENGENAAN PPH PASAL 4 AYAT 2 PADA PERUSAHAAN RETAIL - Ferry Kartawijaya (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Company engaged in retail. Apart from sales, other sources of income come from various types of rents, in this case leasing floor displays. the analysis method is in the form of qualitative analysis. UH Income Tax Article 4 Paragraph 2 regulates that income in the form of deposit interest, and other savings income from stock transactions in other securities on the stock exchange, income from the transfer of property in the form of land and / or buildings and other certain income, tax imposition is regulated by Government Regulation. Based on Government Regulation number 29 of 1996 sttd PP Number 5 of 2002 jo. KMK-394 / KMK.04 / 1996 sttd KMK Number 120 / KMK.03 / 2002 jo. Decree of the Director General of Tax Number KEP-227 / PJ. / 2002 concerning payment of land and building tax stipulates that the amount of income tax that must be deducted and paid for itself is 10% (ten percent) of the gross amount of land and / or building rental value and is final.